Cellulose Oxygen Isotopes of Sphagnum and Vascular Plants in a Peat Core Reveal Climate Change in Northern Japan Over the Past 2, 000 Years. (8th September 2021) - Sakurai, Hiromichi; Yamamoto, Masanobu; Seki, Osamu; Omori, Takayuki; Sato, Tomonori
Abstract: The cellulose δ 18 O of plant tissues in peat is a potential climate proxy. However, understanding what is driving the shifts in δ 18 O of cellulose is required for its application. Here, we analyzed the δ 18 O values of Sphagnum and vascular plant cellulose, as well as the δ 18 O and δD values of pore water, in a 4‐m‐long peat core from the Bekanbeushi ombrotrophic bog to understand paleoclimatic changes in northern Japan over the past 2, 000 years. The cellulose δ 18 O values of Sphagnum were lower than those of vascular plant tissues, although both draw water from the same layer. Whereas the cellulose δ 18 O values of Sphagnum more directly reflect those of precipitation, those of vascular plants become enriched through transpiration. Thus, the difference between vascular plants and Sphagnum (Δδ 18 Ovp–sp ) is a potential proxy for relative humidity. Cellulose δ 18 O of Sphagnum revealed centennial variations with maxima around 800, 1300, and 1500 CE and minima around 500, 1000, 1700, and 1900 CE. The Δδ 18 Ovp–sp was inversely correlated with Sphagnum cellulose δ 18 O, indicating that the axis of summer westerlies was more frequently located to the north and the climate was moist in the former periods, whereas the axis of summer westerlies was generally located to the south and the climate was dry in the latter periods. These results suggest a warm and moist climate during the former periods due to frequent rainy summers driven by strong East Asian summer monsoon activity, and the opposite conditions in the latter periods. Plain Language Summary: The cellulose oxygen isotopes of plant tissues in peat preserve information about rainwater and its climatic background, but no definite method of interpreting these data has been established. Our analysis of a peat core from northern Japan indicates that Sphagnum moss tissues have lighter isotopic compositions than the tissues of grasses and dwarf shrubs, despite a common water source. Sphagnum more directly reflects the isotopic composition of rainwater, whereas grasses and dwarf shrubs are enriched in 18 O due to preferential loss of 16 O during transpiration. Thus, their difference reflects past moisture conditions. The cellulose oxygen isotopic composition of Sphagnum exhibited centennial variations. Because the rainwater oxygen isotopic composition of rainwater is sensitive to changes in the position of the westerly wind axis, its variations indicate past latitudinal shifts of the westerlies. When the axis was located in the north, moist conditions were indicated by the difference between Sphagnum and grass isotopes. This finding suggests that the position of westerly winds and moisture transport from the south were linked and together shaped the paleoclimate of northern Japan. Key Points: Cellulose oxygen isotopes in a peat core were evaluated to understand the paleoclimate of northern Japan The cellulose oxygen isotopic ratios of Sphagnum and vascular plants are useful to reconstruct the position of westerlies and humidity The results show changes in atmospheric dynamics affecting summer rainfall in northern Japan on a centennial timescale